Feasibility studies on the storage capacity augmentation of Kambalathara ERI of Chittur Puzha project and its impacts on irrigation development - HARIKRISHNAN R; Heera P. A; Jineesh R; Vimitha T; Dr. Rema K. P (Guide) (Tavanur 2014 Department of Irrigation & Drainage Engineering)
Feasibility studies on the storage capacity augmentation of Kambalathara ERI of Chittur Puzha project and its impacts on irrigation development
Feasibility studies on the storage capacity augmentation of Kambalathara ERI of Chittur Puzha project and its impacts on irrigation development